Law No. 7 of the year 2025 Amending Certain Provisions of the Uniform Tax Procedure Law Promulgated by Law No. 206 of the year 2020 = قانون رقم 7 لسنة 2025 بتعديل بعض أحكام قانون الإجراءات الضريبية الموحد الصادر بالقانون رقم 206 لسنة 2020 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic